PENDIDIKAN TAUHID DALAM NASKAH HET BOEK VAN BONANG PENDEKTAN FILSAFAT PENDIDIKAN ISLAM - Waluyo Waluyo (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2023)
Het Boek van Bonang is one of several texts which have been used as historical sources for the truth of Walisongo's existence. This research is motivated by the author's interest and the uniqueness of the Het Boek van Bonang manuscript which is a source of Islamic teachings attributed to Sunan Bonang. Efforts to uncover the essence of monotheism education in texts use an educational philosophy approach. The educational philosophy method is the formal object of this study, in the analysis using the ontology, epistemology and axiology approaches. The results to be achieved in this study are what and how is the essence of auhid education in the texts of Sunan Bonang. This study found that Sunan Bonang's educational teachings were about the importance of believing in God with the teachings of monotheism (oneness of God). The teaching of Oneness through understanding the meaning of the shahada in each of its da'wah education.